Valuing urban green spaces for enhanced public health and sustainability: A study on public willingness-to-pay in an emerging economy - Bressane, Adriano [UNESP]; Galvão, Amanda Louisi dos Santos [UNESP]; Loureiro, Anna Isabel Silva [UNESP]; Ferreira, Maria Eduarda Guedes [UNESP]; Monstans, Monique Casagrande [UNESP]; Medeiros, Líliam César de Castro [UNESP] (My University, 2024)
Statement of problem: Rapid urbanization threatens urban green spaces (UGS), impacting ecological sustainability and public health. Research gap: There is a notable research gap in understanding public willingness to pay (WTP) for UGS in developing countries, including Brazil, which this study addresses. Purpose: This study aims to explore the association between public WTP for UGS and the recognition of their health benefits in Brazil, contributing to urban sustainability and public health. Method: Employing a mixed-methods approach, the study integrates statistical quantitative analysis of WTP through surveys with qualitative insights into public perceptions of UGS benefits. Results and conclusions: The findings reveal a significant willingness among the public to pay for UGS, driven by the recognition of their health benefits. The study underscores the importance of UGS for urban well-being and sustainability, highlighting a strong correlation between health benefits recognition and WTP. Practical implications: The results inform urban planners and policymakers of the critical value placed on UGS by the public, suggesting the need for inclusive urban development policies that prioritize green space accessibility and maintenance. Future directions: Further research is recommended to explore innovative funding mechanisms for UGS to ensure equitable access and sustainability, alongside the impact of educational programs on public support for UGS.
Keywords: Brazil; Public health; Sustainable urban development; Urban green spaces; Willingness to pay